Toll-like receptors in breast cancer immunity and immunotherapy - Zhou, Joseph; Zhang, Lin; Liu, Siyao; DeRubeis, David; Zhang, Dekai (Frontiers in Immunology, 2024)
Toll-like receptors (TLRs) are a key family of pattern recognition receptors (PRRs) in the innate immune system. The activation of TLRs will not only prevent pathogen infection but also respond to damage-induced danger signaling. Increasing evidence suggests that TLRs play a critical role in breast cancer development and treatment. However, the activation of TLRs is a double-edged sword that can induce either pro-tumor activity or anti-tumor effect. The underlying mechanisms of these opposite effects of TLR signaling in cancer are not fully understood. Targeting TLRs is a promising strategy for improving breast cancer treatment, either as monotherapies or by improving other current therapies.Here we provide an update on the role of TLRs in breast cancer immunity and immunotherapy.